Inaktivasi Askospora Talaromyces Sp. Dalam Jus Nanas Menggunakan Proses Termal - Doni Fozla; Evelyn Evelyn; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Talaromyces sp. is a heat resistance mold. Talaromyces sp. ascospore can survive after pasteurization and germinate in low pH fruit juices. Food preservation by thermal processing is a conventional treatment method and is still often applied today. The aim of this study was to investigate the effect of temperature (T: 85 °C, 88 °C, 91 °C) and soluble solid content (SS: 10 °Brix, 20 °Brix, 30 °Brix) on the thermal inactivation of Talaromyces sp. Ina-CC F155 ascospore. It was found that the ascospore log reduction increased with increasing temperature. For example, at SS; 10 °Brix there was a reduction of 2.5 log after 22.3 minutes for 85 °C, 14.3 minutes for 88 ° C and 9.3 minutes for 91 °C. in contrast, increasing soluble solid content resulted in the increases of Talaromyces sp. ascospore resistance in pineapple juice. The results of this study emphasize the importance of temperature and soluble solid content for heat resistance of Talaromyces sp. ascospore in juice.Keywords: ascospore, inactivation, pasteurization, thermal process, Talaromycessp.